2. Venlafaxine and oxycodone have different effects on spinal and supra-spinal activity in man. Issue 12 (December 2016) - Valeriani, M.; Lelic, D.; Fischer, I.W.D.; Dahan, A.; Drewes, A.M.
Abstract : This study aimed to explore how oxycodone (opioid) and venlafaxine (SNRI) modulate somatosensory processing. Twenty volunteers were included in this randomized, cross-over, double blinded experimental study comparing treatment with venlafaxine and oxycodone to placebo. Spinal and full scalp cortical somatosensory evoked potentials (SEPs) to median nerve stimulation were recorded before and after five days of treatment. In the venlafaxine arm, the P11 and N60-80 latencies were reduced (P < 0.01), whereas the P25 amplitude was decreased (P = 0.01). Oxycodone increased the P14 (P = 0.03) and N30 (P = 0.04) amplitudes and the N60-80 latency (P < 0.05). The brainstem and primary somatosensory cortex source strengths were increased in oxycodone arm, whereas the primary somatosensory cortex strength was decreased in venlafaxine arm (P < 0.05). Opioids and SNRIs exert different central effects.